Pengaruh Hubungan Tren TikTok terhadap Pembelian Produk Online di Bojonegoro - Jihan Agusta Anis Vabella; Komarun Zaman; Aisyah Darti Megasari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of TikTok trends on online product purchases in Bojonegoro Regency. The background of this research is based on the phenomenon of increasing use of TikTok as a social media that not only functions as entertainment, but also as a means of product promotion that has an impact on consumer behavior. The method used is a quantitative approach with simple linear regression analysis. The research sample amounted to 44 respondents who were selected through purposive sampling techniques, with the criteria of active TikTok users who have made online product purchases in the last three months. Data collection was carried out through an online questionnaire using the Likert scale, and the research instruments have been tested for validity and reliability. The results of the analysis showed that the TikTok trend had a significant effect on the purchase of online products, with a determination coefficient value (R²) of 0.690. This means that TikTok trends are able to explain 69% of the variation in consumer purchase decisions. These findings support the Stimulus-Organism-Response (SOR) theory, which states that stimuli in the form of TikTok viral content can shape consumer perceptions and responses in the form of purchase decisions. This research provides practical implications for business people to utilize TikTok trends as an effective digital marketing strategy in increasing product sales online.